Pemberdayaan Masyarakat Melalui Implementasi Dana Desa Di Desa Jogjogan Kecamatan Cisarua Kabupaten Bogor - Yuswarni; Yusreni Sabrie; Ummu Salamah (Universitas Darul Ulum, 2022)
Empowerment is essentially a process that can make people more empowered and independent. In mobilizing this independence, of course, support and encouragement are needed to re-awaken their role and position, therefore through Village Law no. 6 of 2014 the government initiated the provision of village fund assistance, which aims as a form of state commitment to protect and empower villages to become strong, advanced, independent and democratic. The Village Fund is prioritized for the development of local economic potential in order to increase the capacity of rural communities in entrepreneurial development, increase income, and expand the economic scale of rural communities. This research was conducted using qualitative methods with descriptive data with the research location in Jogjogan Village, Cisarua District, Bogor Regency. The data collection techniques in this study were through observation, interviews, and documentation studies with the research informants being the village head and other village officials, as well as UMKM actors such as business groups, head of tourism managers, homestay or villa owners. In this study, the analysis technique used an interactive analysis model, namely through data reduction, data presentation, and finally drawing conclusions.